2015
DOI: 10.1007/s00737-015-0549-5
|View full text |Cite
|
Sign up to set email alerts
|

PREPP: postpartum depression prevention through the mother–infant dyad

Abstract: Most interventions to prevent Postpartum Depression (PPD) focus on the mother rather than the mother–infant dyad. As strong relationships between infant sleep and cry behavior and maternal postpartum mood have been demonstrated by previous research, interventions targeted at the dyad may reduce symptoms of PPD. The goal of the current study was to examine the effectiveness of Practical Resources for Effective Postpartum Parenting (PREPP). PREPP is a new PPD prevention protocol that aims to treat women at risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 69 publications
(98 reference statements)
1
71
0
Order By: Relevance
“…52 Two other trials reported statistically significant or near-significant reductions in symptom severity scores at 1 (but not all) of several time points on at least 1 depression screening instrument (but not all). 53,54 Educational interventions and other supportive interventions, such as telephone-based peer support and nondirective group sessions, dem-onstrated inconsistent findings, with 1 of 6 and 3 of 7 trials, respectively, reporting statistically significant reductions in depression status or depression symptom scores. Yoga classes, debriefing exercises, and expressive writing failed to demonstrate statistically significant reductions in depression symptoms or status.…”
Section: Effectiveness Of Preventive Interventionsmentioning
confidence: 99%
“…52 Two other trials reported statistically significant or near-significant reductions in symptom severity scores at 1 (but not all) of several time points on at least 1 depression screening instrument (but not all). 53,54 Educational interventions and other supportive interventions, such as telephone-based peer support and nondirective group sessions, dem-onstrated inconsistent findings, with 1 of 6 and 3 of 7 trials, respectively, reporting statistically significant reductions in depression status or depression symptom scores. Yoga classes, debriefing exercises, and expressive writing failed to demonstrate statistically significant reductions in depression symptoms or status.…”
Section: Effectiveness Of Preventive Interventionsmentioning
confidence: 99%
“…Different forms of psychotherapy are used both as preventive tools for mothers at risk for developing PPD and as interventions when PPD is manifest. Usually, the mother-child dyad is in focus (Werner et al, 2015). Additionally, pharmacological treatment with Selective Serotonin Reuptake Inhibitors (SSRI) can be administered both during pregnancy and to breastfeeding mothers.…”
Section: Discussionmentioning
confidence: 99%
“…There is preliminary evidence that parenting support and anticipatory parenting guidance can prevent postpartum depression. (23) Obstetricians can play a key role in recognizing women with need for additional parenting support and refer to appropriate resources such as home visiting programs or maternity support services, available in most states.…”
Section: Mood Disorders In Pregnant and Postpartum Women Have Tremendmentioning
confidence: 99%